2021
DOI: 10.1002/dmrr.3497
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein‐1 predicts the development of diabetic nephropathy

Abstract: Aim Diabetic nephropathy (DN) is a devastating complication of diabetes mellitus (DM). Therefore, screening strategies in order to prevent its development and/or retard its progression are of paramount importance. We investigated if monocyte chemoattractant protein‐1 (MCP‐1) was associated with new onset microalbuminuria‐the earliest sign of the albuminuric phenotype of DN‐ in patients with type 2 DM and normoalbuminuria. Methods We measured MCP‐1 in serum and urine samples from patients of the Randomized Olme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…High concentrations of glucose induce the secretion of inflammatory cytokine MCP‐1 and leukocyte interleukin‐8 (IL‐8) by activating the reactive oxygen species (ROS) and NF‐κB pathways 5,6 . High serum levels of MCP‐1 and IL‐8 accelerate the progression of diabetes and increase the incidence of complications 7‐9 . As a result, therapeutic agents against ROS have also been widely studied in the treatments of diabetes mellitus 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High concentrations of glucose induce the secretion of inflammatory cytokine MCP‐1 and leukocyte interleukin‐8 (IL‐8) by activating the reactive oxygen species (ROS) and NF‐κB pathways 5,6 . High serum levels of MCP‐1 and IL‐8 accelerate the progression of diabetes and increase the incidence of complications 7‐9 . As a result, therapeutic agents against ROS have also been widely studied in the treatments of diabetes mellitus 10 …”
Section: Introductionmentioning
confidence: 99%
“…5,6 High serum levels of MCP-1 and IL-8 accelerate the progression of diabetes and increase the incidence of complications. [7][8][9] As a result, therapeutic agents against ROS have also been widely studied in the treatments of diabetes mellitus. 10 There is convincing evidence of the benefit of vitamin D on antioxidation.…”
Section: Introductionmentioning
confidence: 99%
“… 20 22 23 Using a larger participant cohort in a recent post hoc analysis of the ROADMAP (Randomized Olmesartan and Diabetes Microalbuminuria Prevention) study revealed that even despite very high variations in outcome, serum and urinary MCP-1 levels were significant predictors of the onset of albuminuria in patients with diabetes. 36 …”
Section: Discussionmentioning
confidence: 99%
“…20 22 23 Using a larger participant cohort in a recent post hoc analysis of the ROADMAP (Randomized Olmesartan and Diabetes Microalbuminuria Prevention) study revealed that even despite very high variations in outcome, serum and urinary MCP-1 levels were significant predictors of the onset of albuminuria in patients with diabetes. 36 Only in the Dutch participants, a positive association was found between urinary HPSE-1 activity and albuminuria levels. Several studies found increased HPSE-1 activity levels in patients with diabetes 24 25 but only one study found a correlation between urinary HPSE-1 activity and the degree of albuminuria.…”
Section: Pathophysiology/complicationsmentioning
confidence: 91%
“…Some chemokines have been shown to be involved in the pathogenesis of DR. In some recent studies, monocyte chemotactic protein-1 (MCP-1) and macrophage inflammatory protein-1 alpha (MIP-1a) have been reported to be elevated in diabetic patients [ 14 , 26 , 27 ]. Moreover, a level of other inflammatory cytokines such as interleukin 1 (IL-1), IL-6, IL-8, and tumor necrosis factor alpha (TNF-α) was upregulated in diabetic patients with DR. Additionally, there is a correlation between the presence of high levels of growth factors and inflammatory cytokines in the eye fluids and inflammation in patients with DR.…”
Section: Pathology In Drmentioning
confidence: 99%